Synthesis and SAR studies of pyrazole-3-carboxamides and -3-carbonyl thioureides including chiral moiety: Novel candidates as antibacterial agents - Bildirici Ishak; Cetin Adnan; Menges Nurettin; Alan Yusuf (Journal of the Serbian Chemical Society, 2018)
A series of tetrasubstituted pyrazole-3-carboxamides (3a–c) and pyrazole- 3-carbonyl thioureides (6a–c) were synthesized and their structures characterized by IR, NMR and elemental analysis. The antibacterial potential against specific Gram-positive and Gram-negative strains and the antifungal activities of all novel compounds were investigated. Structure–activity relationships (SAR) studies and some theoretical parameters (ClogP, CMR, PSA and ESP) of the compounds were performed on these two pyrazole derivatives. Pyrazole-3-carboxylate ester 2 was used for the synthesis of the carboxamide derivatives. The reactions of pyrazole-3-carbonyl isothiocyanate 5 with appropriate chiral amino alcohols were utilized for synthesizing the thioureide derivatives. Both of these types of pyrazole derivatives including a chiral moiety exhibited pronounced antibacterial activities. According to the present in vitro study, some of the promising compounds might be new candidates for a new generation of antibacterial drugs.